Instilling Social Norms Through PPKn Learning in Elementary Schools - Alam, Muhammad Bahrul; Muhroji, M (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to describe how teachers instill social norms to overcome and improve students' morals through Pancasila and Citizenship Education (PPKn) at Muhammadiyah Alam Surya Mentari Elementary School. Methodology: This study uses a qualitative methodology with a descriptive approach, combining observation and observation as data collection techniques to understand the role of teachers in instilling social norms in grade 4. Results: This study revealed that social norms are formed through collaborative learning and discussion activities, helping individuals understand the importance of social norms in everyday life. Factors that influence social norms in today's children are due to technological advances and the lack of parental roles in shaping children's characters. In instilling social norms, teachers provide varied learning and the important role of parents in shaping children's characters. Applications/Originality/Value: This study highlights the greater correlation between schools and parents which ensures good management in home and school environment in shaping the character and morals of students for the better.